Free Cash Flow Moderated Income Smoothing, Earning Persistence Toward Earnings Response Coefficient - Verawaty, Verawaty; Rahmawati, Sistya; Mulwaningsari, Etty (CV. AFDIFAL MAJU BERKAH, 2024)
The aim of this study is to investigate: (1) the effect of income smoothing, earnings persistence, and systematic risk on ERC; (2) whether free cash flow moderates the relationship between income smoothing, earnings persistence, and systematic risk on ERC; (3) the influence of income smoothing, earnings persistence, and systematic risk on free cash flow; (4) how these factors affect free cash flow; and (5) the impact of free cash flow on ERC. The research uses a quantitative approach, drawing on secondary data from energy and mineral companies listed on the Indonesia Stock Exchange, with purposive sampling criteria for the 2018-2021 period (4 years). The findings reveal that (1) income smoothing, earnings persistence, and systematic risk do not have a significant impact on ERC; (2) free cash flow does not serve as a moderating variable, as it does not amplify the effect of income smoothing, earnings persistence, and systematic risk on ERC; (3) earnings persistence affects free cash flow; and (4) free cash flow influences ERC. The originality of this study lies in its contribution to transparency literature, demonstrating that (1) the market's reaction to earnings information is not linked to financial statement manipulation, with the market responding more to the availability of funds for investors.